Empirical Models for Indoor Propagation in CTU Prague Building - Pechač, Pavel; Klepal, M. (Radioengineering Society, 2000)
Indoor propagation modelling is demanded for the design and maintenance of indoor wireless services. Empirical modelling seems to be the most efficient approach. Even so there are many studies dealing with empirical models for indoor propagation, the results can be hardly used for local buildings without modifications. There are several specific architecture styles and used materials. The indoor propagation measurement campaigns in the frequency range of 900 MHz were done in two typical multi-storey university buildings in Prague. Based on the measurement results, the easy-to-use empirical propagation prediction were derived for both of the buildings with satisfactorily accuracy. variations of the models were studied. The models are being implemented into a CAD software tool for complex design of indoor cellular systems. The project continues using a similar approach for other frequency bands. In the same time, other novel ways of semi-empirical modeling of indoor propagation are investigated.
Keywords: indoor propagation; electromagnetic waves; modelling; measurement; personal wireless systems